Flipbook Online Majalah Komunikasi Universitas Negeri Malang (UM) Berbasis Website Sebagai Media Publikasi Internal dan Eksternal Kampus - Sholihah, Nida Anisatus; Hadi, Djajusman; Nasution, Zulkarnain (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Mass media has significant roles in society and acts as a communicator as well as a pioneer of changes in the public environment that can influence society through messages in the form of information, and entertainment. According to Indonesian Internet Service Providers Association (Asosiasi Penyelenggara Jasa Internet Indonesia/APJII), people in the age range of 19-34 years old are the main users of the internet with a percentage of 49,52%, making the highest number of internet users are in their productive age. Therefore, along with the printed version, Majalah Komunikasi provides the website-based online flipbook. This research aims to make it easier for UM academic community to provide effective and practical services in obtaining information and the latest campus news. Through the implementation of this online flipbook, UM academic community will not miss the latest valid and in-depth campus information because it can be accessed remotely easily and practically as if opening a printed magazine but in a digital way. This study conducted the ADDIE (Analyze, Design, Development, Implementation, Evaluation) method. Other than facilitating academics in receiving the campus’s latest information, this online flipbook is more economical because it is paperless and can save up more expenses. Besides, the implementation of the online flipbook can fulfill the requisitory data of Student Affair Ranking System (Sistem Pemeringkatan Kemahasiswaan/Simkatmawa) as a winner’s additional contribution because through this online flipbook, Majalah Komunikasi won 1st place at a national level event, namely the Indonesia Print Media Awards (Isprima) organized by the Central Press Company Union (Serikat Perusahaan Pers/SPS). This will definitely impact Simkatmawa so that UM’s national rank can be escalated.